Empowering public health awareness through dissemination of traditional medicine products - H. Hardani; Adriyan Suhada; Tuhfatul Ulya; Ajeng Dian Pertiwi; Rosnalia Widyan; Wulan Ratia Ratulangi; Palanee Ammaranond (Universitas Muhammadiyah Malang, 2024)
Traditional medicines have been an integral part of the cultural heritage and health systems of various societies around the world. To promote the use of traditional medicine and understand it more deeply, the dissemination of traditional medicine products is a crucial step. The purpose of this service is to explore the importance of the dissemination of traditional medicinal products and their benefits to the community. The main target of this activity were people who have a history of chronic disease. In addition, public awareness to obtain information related to traditional medicine products was still lacking. The method of implementing this service activity was carried out by providing direct education related to traditional medicine to the community. As a result of the service, 19 traditional medicine products were disseminated and increased public awareness about traditional medicine. This result implies that the use of traditional medicine should be widely encouraged to a larger community.